Uma contribuição ao processo decisório na definição de projetos no âmbito dos conselhos participativos para inclusão no orçamento do município de São Paulo - Saliba, Marilia Cassia Teixeira (2016)
In recent years, Public Administration has undergone several changes aimed at controlling public spending and accountability of public officials with public resources. Such changes started with the publication of Law 101/2000, and, concomitantly to these legal changes, came the Brazilian Accounting Standards Applied to the Public Sector (NBCASP) that began in 2008 with the publication of the first standards. In this sense, the roles of the Public Management and Public Accountant become imperative. The judicious decision-making processes in the public sphere became critical and, combined with the tools of Public Accounting, are essential to make the best decision. It is important to note that with the participatory management, decisions are proposed, in many cases, wit the participation council members, elected by the population, who generally do not have sufficient expertise to make the most priority decision and need a tool to assist them in the decision making process. It was for this reason that the present work was developed, with the intention to make a contribution in these times of great change. One of the major problems in public management is the mechanism used in the decision making process, so the paper proposes a method of prioritizing it, adapting the work of Nunes and Pinheiro (2008) for financial and banking institutions, that can be used for all sectors. The work of Jannuzzi, Miranda and Silva (2009) that shows the method of Multi-criteria Decision Support (MDS) for Public Policy was also incorporated. The adapted method studied projects or demands, and actions, submitting them to a multiple criteria evaluation that consisted in the use of five criteria, each composed of five attributes that received scores from 1 to 5, in order to measure the degree of priority of each attribute. In the end, the data set was organized in a table that shows be which project should prioritized first. The composition of the prioritization criteria has taken into account the concept of cost to serve in the reverse perspective used in private accounting, meaning that projects that require greater resources in the view of the customer-citizen can get the biggest priority, because they indicate the need for public policies for a given region. Another criterion was the Expected Benefits that assesses, both quantitatively and qualitatively, how that particular project will contribute to the purposeful development of that particular action for the population. The method was tested in Chapel of Socorro neighborhood public administration office, taking the 11 approved projects for the year 2014 and checking which of these had the highest priority